Epidural Analgesia in the Surgical Correction of Pediatric Scoliosis - Nóbrega, Sónia Dória (2020)
Introduction: Pediatric scoliosis surgery aims at stopping the progression of the disease and improving quality of life, however it is associated with a severely painful postoperative period. In 2016, we implemented a clinical protocol with postoperative continuous epidural analgesia, by one or two epidural catheters placed by the surgeon at the end of surgery. The aim of our study was to evaluate the analgesic effectiveness of the epidural protocol up to 72 hours after surgery, the incidence of adverse events and the length of Intensive Care Unit (ICU) stay. Methods: A retrospective analysis was performed by consulting the patients’ clinical files, comparing two groups: Alfentanil group (AG)- 25 patients with systemic opioid analgesia through an alfentanil intravenous infusion - and Epidural group (EG) - 21 patients with epidural ropivacaine and morphine infusion. Data were analyzed using SPSS® , using Nonparametric Mann-Whitney test, Fisher’s exact test and Spearman’s correlation coefficient. A level of significance α=0.05 was considered. Results: The mean pain scores (0-10 numeric rating scale) of the EG were statistically lower at immediate postoperative (-3), 24 hours (-5) and 48 hours (- 4) after surgery (p<0.001), as were the needs for rescue analgesia (p<0.001). There were fewer adverse events in the EG, not reaching statistical significance. ICU length of stay was statistically shorter with epidural analgesia (p<0.001). Conclusion: Epidural analgesia is an effective alternative to systemic opioid analgesia for pediatric scoliosis surgery. Prospective randomized studies are needed to confirm these results.